The role of birth cohorts in long‐term trends in liver cirrhosis mortality across eight European countries. (28th October 2016) - Trias‐Llimós, Sergi; Bijlsma, Maarten J.; Janssen, Fanny
Abstract: Background and aims: Understanding why inequalities in alcohol‐related mortality trends by sex and country exist is essential for developing health policies. Birth cohort effects, indicative of differences by generation in drinking, have rarely been studied. This study estimated the relative contributions of birth cohorts to liver cirrhosis mortality trends and compared sex‐ and country‐specific cohort patterns across eight European countries. Design: Time–series analysis of population‐level mortality data. Setting: Austria, Finland, Hungary, Italy, the Netherlands, Poland, Spain and Sweden; 1950–2011. Participants: National populations aged 15–94 years. Measurements: We modelled country‐ and sex‐specific liver cirrhosis mortality (from national vital registers) adjusting for age, period and birth cohort. Findings: Birth cohorts (adjusted for age and period) made statistically significant contributions to liver cirrhosis mortality in all countries and for both sexes ( P < 0.001), and more so among women (average contribution to deviance reduction of 38.8%) than among men (17.4%). The observed cohort patterns were statistically different between all but two country pairs ( P < 0.001). Sex differences existed overall ( P < 0.001), but not in the majority of countries ( P > 0.999). Visual inspection of birth cohort patterns reveals birth cohorts at higher risk of liver cirrhosis mortality. Conclusions: The inclusion of the birth cohort dimension improves the understanding of alcohol‐attributable mortality trends in Europe. Birth cohorts at higher risk of liver cirrhosis mortality were born during 1935–49 in Sweden and Finland, around 1950 in Austria and the Netherlands and 1960 or later in Hungary, Italy, Poland and Spain.